Cryptococcus neoformans and Cryptococcus gattii Species Complex Isolates on the Slopes of Mount Etna, SICILY, Italy - Trovato, Laura; Oliveri, Salvatore; Esposto, Maria Carmela; Prigitano, Anna; Romanò, Luisa; Cogliati, Massimo (Frontiers in Microbiology, 2019)
This study investigated the presence of Cryptococcus neoformans and Cryptococcus gattii species complex isolates on olive trees growing in the Eastern part of Sicily (Italy) characterized by the presence of the volcano Etna and the ability of these fungal pathogens to sexually reproduce on medium containing volcanic soil. Samples from 124 olive trees were collected from 14 different sites around Mount Etna. Eighteen trees (14.5%) resulted colonized by C. neoformans VNI-alpha A isolates, one (0.8%) by VNIV-alpha D isolates, and two (1.6%) by C. gattii VGI-alpha B isolates. The ability of environmental and reference strains belonging to VNI, VNIV and VGI molecular types to sexually reproduce on a medium containing volcanic soil was also tested. VNI and VNIV strains were able to produce filaments and basiodiospores more vigorously than on the control medium, whereas VGI strains were not fertile. In conclusion, the present study identified which C. neoformans and C. gattii species complex genotypes are circulating in Eastern Sicily and confirmed the ecological role of olive trees as environmental reservoir of these pathogens. It also showed that Cryptococcus is able to colonize and sexually reproduce in inhospitable environments such as the slopes of a volcano.